Product Category Priming – A Case Study on Chocolate - Enrique Strelow; Mark Heitmann; Simone Kühn (Marketing Review St.Gallen, 2020)
Any supermarket visit involves a series of consecutive product choices. These various product categories can prime memory associations. This paper studies how exposure to higher (pralines) vs. lower quality (chocolate bars) product categories drives interest and demand for a target chocolate product (duplo, Giotto).
Keywords: 650